Comparative evaluation of topical phenytoin versus povidone iodine dressing in the healing of diabetic foot ulcers: a randomized controlled trial - Hemanth, Pulivarthi Aakaash; K., Ramappa; Bhalki, Nagaraja; Thrivikrama Rao, Poluru; Aakaash Revanth, Pulivarthi; Pradeep Patil, Shreya; Ashish, R. (International Surgery Journal, 2025)
Background: Diabetic foot ulcers (DFUs) are a crucial diabetes consequence that frequently leads to slow healing, infection and the need for amputation. Povidone iodine (PVP-I) is a widely used antiseptic, whereas phenytoin has lately emerged as a promising wound healing agent due to its proliferative and antibacterial effects. Hence the current study aims to compare the efficacy of topical phenytoin and povidone iodine dressings in promoting healing of diabetic foot ulcers. Methods: A randomized controlled trial was conducted at Navodaya Medical College Hospital, Raichur among 124 patients with grade 1 or 2 diabetic foot ulcers were randomly assigned to two groups which are Group A (phenytoin dressing) and Group B (povidone iodine dressing). Ulcer area was measured at baseline and on Days 3, 5, 7, 10 and 14. Percentage reduction in ulcer area, slough clearance and granulation tissue formation was measured and subjected to statistical analysis. Results: Both groups showed significant reduction in ulcer area by Day 14, with greater improvement in Group A (22.03±9.86%) than in Group B (13.85±5.62%) (p=0.001). Mean absolute reduction in ulcer area was higher in the phenytoin group (6.03 mm² vs. 3.99 mm², p=0.004). Slough clearance was achieved in 95.2% of patients in Group A versus 82.3% in Group B. Granulation tissue appeared earlier and was more robust in Group A. No significant adverse effects were reported. Conclusions: Topical phenytoin dressing is significantly more effective than povidone iodine in accelerating up the healing of diabetic foot ulcers.